THU0138 Pharmacokinetics of fostamatinib in patients with impaired renal function: A phase I study. (23rd January 2014) - Martin, P.; Oliver, S.; Gillen, M.; Marbury, T.; Millson, D.
Abstract : Background: Fostamatinib (R788), a spleen tyrosine kinase inhibitor, is currently being developed as an oral therapy for patients with rheumatoid arthritis 1 . In humans, orally administered fostamatinib is converted to the active moiety, R406. Elimination into the urine accounts for 19% of the administered dose (<1% of dose is excreted as R406 in urine) with 80% of the total drug recovered in faeces 2 . We hypothesised that renal impairment would not affect R406 exposure. Objectives: To assess R406 pharmacokinetics in healthy subjects and subjects with renal impairment. Methods: A total of 24 subjects were enrolled in the phase I study (NCT01245790 ) and stratified into three equal groups based on creatinine clearance rates (CLCR ) as follows: normal renal function (CLCR ≥80 mL/min), moderate renal impairment (CLCR ≥30 to <50 mL/min), and end-stage renal disease (ESRD; requiring dialysis). Subjects with normal renal function and ESRD were enrolled first, followed by the group with moderate renal impairment. Subjects with normal and moderate renal function received a single oral dose of 150 mg fostamatinib, while those with ESRD received two oral doses of 150 mg fostamatinib with a 1-week washout period between doses. The first dose was taken post-dialysis and the second dose 2 h pre-dialysis. Blood samples were collected pre-dose and up to 72 h post-dose. Urine was collected pre-dose from –12 to 0 h, and during 6-h intervals up to 48-h post-dose to determine the concentrations of R406 and its N-glucuronide metabolite. Results: R406 Cmax and AUC geometric means were lower in the renally impaired groups when compared to the normal renal function group while the median tmax was similar across all treatment groups. In ESRD subjects, R406 exposure was lower post-dialysis compared with pre-dialysis. Urinary excretion of R406 N-glucuronide was lower with increasing severity of renal impairment. Renal elimination of R406 was negligible (less than 0.1% of administered dose) in all treatment groups. There were no statistically significant relationships between R406 exposure and CLCR. Eleven subjects reported ≥1 adverse event with nausea being the most common. There were no deaths or serious adverse events reported. Conclusions: Renal impairment did not affect the exposure of the active metabolite R406 to an extent that would be considered clinically relevant. Consequently, there is no expectation of a need for fostamatinib dose reduction in renally impaired subjects. References: Baluom M, et al. Clin Pharmacol 2011;51:1310–1318. Sweeny DJ, et al. Drug Metab Dispos 2010;38:1166–1176. Disclosure of Interest: P. Martin Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, S. Oliver Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, M. Gillen Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, T. Marbury: None Declared, D. Millson Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals